ECOLABELING AND ITS INFLUENCE ON CONSUMER PURCHASE INTENTION - do Nascimento, Talles Silva; da Silva, Hermes Moretti Ribeiro [UNESP]; Spers, Eduardo Eugênio; de Lima, Lilian Maluf; Borodai, Mariângela Gallina (University Nove de Julho, 2025)
Objective: The general objective of this study is to analyze the influence of ecolabeling on the purchase intention of orange juice consumers. Method: Quantitative approach carried out in two stages: the first exploratory, with in-person eye monitoring (eye tracker), and the second explanatory, with the application of online questionnaires. The analyses involved structural equation modeling, logistic regression and neuroscientific (eye tracker) techniques to understand the purchase intention of consumers. Results: The results indicated that attitude and perceived behavioral control positively influence the intention to purchase eco-labeled products, while subjective norm has a negative impact. The inclusion of pro-environmental behavior garnered a positive influence. Theoretical contributions: The present study contributed to the literature by testing an integrated model of the Theory of Planned Behavior with the inclusion of important constructs for sustainability, such as pro-environmental behavior and the identification of greenwashing. Furthermore, the use of the eye tracker reveals how consumers direct visual attention to product attributes, improving the understanding of the perception of ecolabeling. Managerial contributions: The findings of this study can be of use to companies and organizations seeking to further promote sustainable practices in their activities and products. Relevance: Investigating ecolabelling and its attributes helps researchers and other interested parties to understand its relevance in terms of consumer purchasing intention, in addition to minimizing its negative environmental effect.
ROTULAGEM ECOLÓGICA E SUA INFLUÊNCIA NA INTENÇÃO DE COMPRA DOS CONSUMIDORES
Keywords: Consumer behavior; Ecolabeling; Greenwashing; Purchase intention